Ants, or Moths? Insects to be found in the manichean Kingdom of Light, according to the parthian Huyadagman I.18 - Băncilă, Ionuţ Daniel (Archaeus, 2009)
Central and Eastern European Online Library - CEE journals, documents, articles, periodicals, books available online for download, Zeitschrfitendatenbank, Online Zeitschriften, Online Zeitschriftendatenbank